Access and engagement of First Nations women in maternal and child health services - Austin, Catherine (Federation University Australia, 2023)
This thesis explores and describes the engagement of First Nations women, with children from birth to five years of age, with Maternal and Child Health (MCH) services in Victoria, Australia. Identification of the factors that facilitate, support or hinder these women’s engagement with MCH services could strengthen the model of care to effectively engage First Nations women with these services. Access in the early years of a child’s life to integrated, effective, community-based services is a well-established predictor of a child’s successful transition to school and their lifelong education and employment outcomes. Such access is crucial in a child’s first 2,000 days (the period from conception to the child’s fifth year), which forms the foundation for a child’s lifetime development and health. Prior evaluative studies have shown that participation in MCH services in Victoria improves the health outcomes for children and families, particularly First Nations families. However, First Nations women and their children in Victoria show poorer health outcomes and lower participation in MCH services compared to non-Indigenous persons; this suggests a need to improve the current Victorian MCH service model. This thesis contributes recommendations for such improvements. The literature review (Chapter 2) identified the absence of a synthesis of qualitative studies of models of care to help guide MCH practice and innovation for all families, especially those at risk of child abuse and neglect. To address this gap, a three-phase qualitative study was conducted in the Glenelg Shire, Victoria, Australia, using narrative inquiry integrated with the Indigenous philosophy ‘Dadirri’. ‘Dadirri’, which emphasises deep and respectful listening, guided the development of the research design; this methodology assisted in understanding Indigenous culture and its sensitivities, building trust with the First Nations peoples involved in the studies, developing open-ended and conversational dialogue, and building respectful relationships. ...